The ideology of agribusiness in basic education - Victor Hugo Junqueira; Maria Cristina dos Santos Bezerra (Universidade Federal de Santa Catarina, 2018)
Agribusiness has become a reality in the Brazilian countryside since the 1990s. However, its performance is not limited to the production and commercialization of goods at the international level. In this sense, starting from the Marxist concept of ideology as a representation of the social relations of production and component of the class struggle, with material interferences in the reproduction of the relations of production, we analyze agribusiness as the ideological expression of the ruling class. We bring arguments of the agribusiness discourse and its use in the educational program 'Agribusiness in School' developed by the Brazilian Association of Agribusiness in the region of Ribeirão Preto-SP. The results show the importance of education as an ideological tool to internalize in the subjects' consciousness, since childhood, the social importance of the agribusiness to ensure the reproduction of production relations.